2010
DOI: 10.1007/s11738-010-0526-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and rapid plant regeneration of oil palm zygotic embryos cv. ‘Tenera’ through somatic embryogenesis

Abstract: An efficient and rapid plant regeneration system through somatic embryogenesis was developed using 13-week-old zygotic embryos of oil palm (Elaeis guineensis Jacq.) cv. 'Tenera'. Zygotic embryos were cultured on MS and N6 media supplemented with 2.0 mg L -1 picloram, 2,4-D and dicamba. The highest embryogenic callus formation (32%) was observed on N6 medium with 2,4-D after 3 month culture on callus induction medium. Somatic embryos were continuously formed from nodular calli on embryo maturation medium [N6 ? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 16 publications
8
40
1
12
Order By: Relevance
“…Alternatively, B5 medium has been used for the in vitro regeneration of Arabidopsis thaliana (Gaj, 2001). Furthermore, Thuzar et al (2011) revealed that using N6 medium in in vitro cultures promoted somatic embryogenesis and plant regeneration of Elaeis guineensis Jacq. As well as these, somatic embryogenesis of Agave tequilana has been reported when cultured on Schenk and Hildelbrant (SH) medium (Rodríguez-Sahagún et al, 2011).…”
Section: Culture Mediummentioning
confidence: 99%
“…Alternatively, B5 medium has been used for the in vitro regeneration of Arabidopsis thaliana (Gaj, 2001). Furthermore, Thuzar et al (2011) revealed that using N6 medium in in vitro cultures promoted somatic embryogenesis and plant regeneration of Elaeis guineensis Jacq. As well as these, somatic embryogenesis of Agave tequilana has been reported when cultured on Schenk and Hildelbrant (SH) medium (Rodríguez-Sahagún et al, 2011).…”
Section: Culture Mediummentioning
confidence: 99%
“…The association of ANA, auxins, with a BAP, cytokinin, did not improved the rooting, only the shots formation, suggesting that the rooting step should be performed separately from the shoot production, in order not to interfere with rooting (Thuzar et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…This disturbance was defined as "a phenotypic variation, either genetic or epigenetic in origin, displayed among somaclones, namely plants derived from any form of cell culture involving the use of somatic plant cells" (Schaeffer, 1990). In Tenera oil palm, SEs were also obtained when the embryogenic calli were transferred to N6 maturation medium supplemented with 0.45 µM 2,4-D, 1.8 µM putrescine, 0.5 g.L -1 hydrolyzed casein and 2 g.L -1 AC (Thuzar et al, 2011). For the conversion of somatic embryos into plants, plant growth regulator-free medium was efficient ( Figure 1I and 2F-G).…”
Section: Discussionmentioning
confidence: 99%